Developmental and interactive effects of arsenic and chromium to developing Ambystoma maculatum embryos: Toxicity, teratogenicity, and whole-body concentrations. Issue 2 (17th January 2017) - Gardner, Steven; Cline, George; Mwebi, Nixon; Rayburn, James
ABSTRACT: Anthropogenic activity has contributed to elevated environmental concentrations of arsenic (As) and chromium (Cr). The spotted salamander, Ambystoma maculatum, may be useful for identifying developmental effects produced by exposure to these contaminants as adults breed and larvae develop in water that may contain As or Cr. Three sample sets among 700 developing larvae were exposed to a range of As, Cr, or 2.5:1 mixture of As:Cr concentrations, respectively. From these 700 larvae, samples containing approximately 24 larvae showed different patterns of whole-body As and Cr from individual and mixture exposure. Whole-body As concentrations were 20.27 and 45.4 µg/g dry weight for larvae exposed to 20 mg/L As and 25:10 mg/L As:Cr, respectively, while whole-body Cr concentrations were 24.8 and 22 µg/g dry weight for larvae exposed to 20 mg/L Cr and 25:10 As:Cr, respectively. Observed malformations included edema, tail kinking, facial deformities, and abnormal bending. Twelve-day lethal concentrations for As and Cr in Ambystoma maculatum larvae were 261.17 mg/L and 71.93 mg/L, respectively, while 12-d effective concentrations to induce malformations were 158.82 and 26.05 mg/L, giving teratogenic indices of 1.64 and 2.76 for individual metal exposure. Exposure to a mixture of As and Cr resulted in a response addition and yielded lower lethal and effective concentration values with a teratogenic index of 2.78, indicating that these contaminants are developmentally toxic at lower concentrations when exposed as a mixture. Data demonstrate that As and Cr affect development of amphibian larvae, and that Ambystoma maculatum may be a useful indicator of environmental toxicity for these metals.